Influência dos vieses cognitivos no julgamento dos contadores diante de eventos contábeis que afetam as informações apresentadas nas demonstrações financeiras - Barbosa, Ismael (2017)
For some years now there has been an increase in the investigations seeking to understand how individuals process information, make judgments and take decisions in the field of finance and accounting. Since 2007, accounting standards allowed for greater judgment in the financial statements preparation, as accounting legislation now allows discretion by the accountants in innumerous situations involving assets, liabilities, revenues and expenses. It is common knowledge that decision making in the accounting area has always been marked by the total rationality, which is to say that the decision makers, knowing all the facts, would make choices in the most rational possible way. However, behavioral accounting, through the Theory of Prospects, questions this rationality, stating that even in face of concrete data, the decision-making process may be influenced by behavioral biases, and therefore the choices made could be different from those expected. Thus, the purpose of this research was to analyze the cognitive biases influence (effects of certainty, reflection and isolation) on the accountants’ judgment in the face of accounting events that affect the information presented in the financial statements. With that in mind, a descriptive survey was performed, aimed at accounting area professionals who were studying in any accounting postgraduate course. The survey was composed by 12 questions related to accounting choices and judgment, involving cognitive biases resulting in profit or loss, trying to capture the influence of cognitive aspects in the respondents. Thus, the Chi-square test of adherence was applied to find the results, indicating that accountants are influenced by cognitive biases derived from the prospect theory. The test also showed that they make their judgments and choices with limited rationality, diverging from what was advocated by the theory of expected utility and consistent with what was predicated on the assumptions of prospect theory, and all this corroborates with the findings of Kahneman and Tversky's (1979) research.